Study Of Serum Lipid Profile In Pre-Eclampsia And Eclampsia - Islam, NAF; Chowdhury, MAR; Kibria, GM; Akhter, S (Faridpur Medical College Journal, 2011)
The present study was designed to evaluate the association of lipid profile in pre- eclampsia and eclampsia. This case-control study was carried out in the department of biochemistry, M.A.G. Osmani Medical College, Sylhet, during July 2005 to June 2006. Total 100 study subjects were evaluated, 40 normotensive pregnant women (mean age 24.90 ± 4.04) as normal and 60 already diagnosed preeclamptic & eclamptic women (mean age 24.17 ± 4.90) as study group. Age range was 15-45 years, gestational age 24 weeks to term were included. Patients with pre-existing hypertension were excluded. Serum lipid profile (total lipids, cholesterol, triglycerides, HDL-cholesterol and LDLcholesterol) of hundred women with Pre-eclampsia and Eclampsia (n=60), normotensive women (n=40) were monitored. The preeclampsia was associated with a significant rise in triglyceride (225.6 ± 28.93 vs 165.6 ± 17.22) and fall in HDL cholesterol concentration (42.4 ± 9.29 vs 55.7 ± 7.11), while eclamptic women showed significant fall in HDL cholesterol (41.8 ± 8.79 vs 55.7 ± 7.11) and rise in LDL cholesterol (133.4 ± 11.75 vs 115.2 ± 10.72) as compared to normal pregnant women. Lipid metabolism plays a key role in the pathophysiology of Pre-eclampsia and Eclampsia. Increased triglycerides levels along with decreased HDL-cholesterol levels and delayed triglycerides clearance and high blood pressure are associated with development of preeclampsia and eclampsia. This association may be significant in understanding the pathologic processes of preeclampsia and may help in developing strategies for prevention or early diagnosis of the disorder. Key Words: Preeclampsia; High Density Lipoproteins; Triglycerides; Low Density Lipoprotein. DOI: 10.3329/fmcj.v5i2.6823 Faridpur Med. Coll. J. 2010;5(2):56-59